Effectiveness of Nintendo Wii in functional and health outcomes of individuals with Parkinson’s disease: a systematic review (Fisioterapia e Pesquisa, 2018)
The objective of this study was to conduct a systematic review of the literature on the effectiveness of Nintendo Wii in the improvement of functional and health outcomes of individuals with Parkinson’s disease. A systematic review of the literature was developed following the PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses), with research in MEDLINE, SciELO, LILACS, PEDro through a search strategy that combined the terms Wii, Parkinson’s Disease, rehabilitation, and physical therapy, followed by manual search. Inclusion criteria were: experimental studies or quasi-experiments related to interventions involving the use of Nintendo Wii to improve functional outcomes in individuals with Parkinson’s disease, published until February 2016, without language restriction. The methodological quality of the studies was assessed with the PEDro scale. Of the 701 studies found, we included seven that met the inclusion criteria - most of the articles (57.14%) had bad methodological quality and were quasi-experiments. The results suggest that the use of Wii seems effective to improve functional outcomes (balance, mobility, motor performance and independence) and health (reducing the risk of falls), being more consistent the results for the improvement of balance. Studies with better methodological quality are needed for the establishment of evidence. Standardization on the types of games, intensity and frequency suitable for each type of patient with PD are still required.